Parking Analysis at Banyumanik 2 General Hospital, Semarang City - Khoir, Muhamad Walidul; Setiawan, Muhammad Agus; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2025)
Vehicle movement will be hampered if the available parking space is insufficient to meet the needs of the facility itselfThe method taken in making this final assignment is to use quantitative methods.the total parking revenue in the Banyumanik 2 Hospital area, Semarang City at the time of the research, based on predetermined parking planning, resulted in an estimated parking levy of Rp. 888,000.00,- per 2 hours.This planning results in a total parking pattern of 46 cars and 153 motorcycles. total income during the research was IDR 668,000.00 per 2 hours. Based on parking planning during research with 46 car lots and 153 motorbikes, there is a total planned levy of IDR 888,000.00 per 2 hours.